Environmentally Safe Method of Localization of Soil Pollution in Emergency Situations of Technogenic Nature - Slepuzhnikov, E. D.; Pietukhov, R. A.; Ponomarenko, R. V.; Buts, Y. V. (Visnyk of V. N. Karazin Kharkiv National University. Series Еcоlogy, 2019)
Puporse. Development a method for the localization of emergencies associated with the leakage of volatile toxic liquids, by using the foams with adjustable curing time. Methods. Surface insulation method of the spilled toxic liquid by using the air-mechanical foam. Results. The results of the development a method for the localization of emergencies associated with the leakage of volatile toxic liquids, by using the foams with adjustable curing time are presented. The new scientific result consists in the use of gelation processes, to obtain an insulating agent with a specified time of curing. It has been established that the most effective means that reduce the rate of transition of toxic liquids to the gas phase are those that ensure the liquid surface isolation. It is proposed to use foam with the time of cure that can be adjust ed. Experimentally determined gel times for two gel forming systems (NH4Cl + Na2O • 2,5SiO2 and (NH4)2SO4+ Na2O ∙ 2,5SiO2). On the basis of the data obtained, the concentrations of the gel formulation and the gelation catalyst with the gel time were selected in the interval of 30-60 s. Conclusions. The developed systems allow to achieve a long process of isolation at a lower specific consumption of components. It is shown that the use of the proposed components in the soil is an environmentally safe process.